Pedagogical competencies of teachers applied to teaching learners with hearing difficulties - Akongyam, Merri; Douglas, Fofie; Owusu, Maxwell Kontor; De-Heer, William; Xorsenyo, Agbenyefia (American Journal of Education and Learning, 2023)
Teachers need to possess appropriate pedagogical competencies to be successful in addressing the special needs of students in the classroom so as to ensure their accomplishment in education. This study investigated teachers’ pedagogical competencies applied to teaching learners with hearing difficulties in the Sekyere South District of Ghana. This study adopted the constructivist paradigm using the qualitative approach. The case study design was employed. In this case study, 16 teachers were purposively sampled, and data were collected from them using a self-constructed interview guide. The instrument was pre-tested to provide experiences and opportunities to engage in critical reflection with regards to the interview schedule. The pre-test also gave a fair idea of the responses to be obtained from the field. All the participants were individually interviewed and their responses were analysed using themes that were generated from the data. Results of the study revealed that although teachers used cooperation, elaboration and motivational strategies to teach learners with hearing difficulties, they did not use other equally good strategies such as storytelling, think-pair-share and demonstration. Additionally, the teachers indicated that they required differentiated and constructivist pedagogies in order to teach learners with hearing difficulties effectively in mainstream schools. Authorities in Universities and Colleges of Education should run programs to educate teachers to be competent in differentiated and constructivist pedagogies to enable effective teaching and learning. Finally, teachers should continuously ensure that there is proper seating arrangement and positive teacher-learner relationship in the classroom to promote a good classroom environment.